The Clinical Application of Homocysteine - Bhargava, Seema (Springer Singapore, 2018)
This book helps clinicians to optimally and appropriately utilize homocysteine levels in the diagnosis, prediction and management of and research into vascular disease and many other conditions. It also familiarizes readers with the pathophysiology and clinical implications of hyperhomocysteinemia. Laboratory investigations are gaining importance in the diagnosis and prognosis of patients, and as such, scientists and laboratorians are constantly attempting to identify new markers that will help in earlier diagnosis and better prognostication of conditions with high morbidity and mortality, as well as high prevalence. According to the WHO, developing countries are home to 80% of patients with coronary artery disease (CAD) and stroke - conditions with a mortality second only to cancer. Intensive research in these areas has resulted in the identification of homocysteine (declared the 'marker of the millennium') and several new markers for the diagnosis and prediction of CAD and stroke. The book is a valuable resource for clinicians and consultants in practice, as well as for postgraduate and undergraduate students of medicine, biotechnology and biochemistry.